Macroprudential Capital Regulation and Fiscal Balances in the Euro Area - Nikolay Hristov; Oliver Hülsewig; Benedikt Kolb (Center for Economic Studies and ifo Institute (CESifo), 2024)
We examine the fiscal footprint of macroprudential policy in euro area countries arising through the bond market channel (Reis, 2021). Using local projections, we estimate impulse responses of the fiscal balance to an unexpected tightening in macroprudential capital regulation. Our findings suggest a dichotomy between country groups. In peripheral countries, the cyclically adjusted primary balance ratio deteriorates after a restrictive capital-based macroprudential policy shock. Since banks are important investors in domestic government debt, the shift in the public budget toward higher borrowing after the innovation might pose a threat to financial stability to the extent that sovereign risk increases. By contrast, in core countries, the cyclically adjusted primary balance ratio barely reacts to a sudden tightening in capital regulation.
Keywords: C33; G28; H63; K33; 330; fiscal footprint; macroprudential capital regulation; sovereign-bank nexus; local projections